2017
DOI: 10.1177/1471301217721304
|View full text |Cite
|
Sign up to set email alerts
|

At the intersection of culture: Ethnically diverse dementia caregivers’ service use

Abstract: This study used an ethnocultural approach to explore how cultural factors influenced ethnically diverse dementia caregivers' experiences and use of services. A modified thematic analysis of in-depth interviews with 15 caregivers, ranging in age from 50 to 75 years, including spouses, daughters, sons, cousins, and a friend, from three minority groups-African American, Hispanic, and South Korean caregivers-was conducted by a team of multi-lingual researchers. Caregiver stress was pervasive across all subgroups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…First, the results of Phase 3 suggest that family caregivers gained knowledge about ADRD as a benefit from participating in the SCP Plus. Previous research (e.g., Richardson et al, 2017) on ethnically diverse ADRD caregivers has uncovered the need for and benefits of obtaining more knowledge about ADRD. Previous studies further suggest that African Americans may have less factual knowledge of and report fewer sources of information about ADRD (Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the results of Phase 3 suggest that family caregivers gained knowledge about ADRD as a benefit from participating in the SCP Plus. Previous research (e.g., Richardson et al, 2017) on ethnically diverse ADRD caregivers has uncovered the need for and benefits of obtaining more knowledge about ADRD. Previous studies further suggest that African Americans may have less factual knowledge of and report fewer sources of information about ADRD (Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (e.g. Richardson et al, 2017) have shown that the issues that African American and other ethnically diverse dementia caregivers struggle with often differ from those that caregivers from the dominant culture encounter. For example, Knight and Sayegh (2010), Lindauer, Harvath, Berry, and Wros (2016) as well as Sayegh and Knight (2011) have argued that ancestral family values and life experiences shaped by historical traumas influence and affect African American caregivers.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Research in the past few years suggests a need for multicomponent, psychosocial and/or psychoeducational interventions that address social support and social networks to help caregivers of people with dementia cope with CB (Beinart, Weinman, Wade, & Brady, 2012; Dam et al., 2016; Fields et al., 2016; Martín-Carrasco et al., 2009). Research also points toward the importance of considering the role of cultural values in dementia family caregiving, particularly as they relate to social support (Richardson et al., 2017). By providing more programs aimed at reducing CB, healthcare and social service professionals may help improve caregivers of people with dementia’ social connectivity to their networks as well as improve their overall health.…”
Section: Discussionmentioning
confidence: 99%
“…One blog written by a caregiver living in Southeast Asia was excluded from the sample because the remaining blogs were written by individuals living in Western countries (the United States and the United Kingdom). These Western caregivers most likely share more similar caregiving experiences given similarities in social, cultural, and political factors that drive the availability of resources and health care services in these countries (Richardson et al, 2019).…”
Section: Study Sample and Data Collectionmentioning
confidence: 99%